2008
DOI: 10.1101/gad.1741408
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant chromatin at genes encoding stem cell regulators in human mixed-lineage leukemia

Abstract: Mixed-lineage leukemia (MLL) fusion proteins are potent inducers of leukemia, but how these proteins generate aberrant gene expression programs is poorly understood. Here we show that the MLL-AF4 fusion protein occupies developmental regulatory genes important for hematopoietic stem cell identity and self-renewal in human leukemia cells. These MLL-AF4-bound regions have grossly altered chromatin structure, with histone modifications catalyzed by trithorax group proteins and DOT1 extending across large domains.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
264
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(300 citation statements)
references
References 41 publications
32
264
4
Order By: Relevance
“…This increased FLT3 expression in the absence of FLT3-activating mutations suggests that the constitutive overexpression of FLT3 is a result of aberrantly increased transcription of FLT3 and it is not due to FLT3-activating mutations. This is supported by Guenther et al, 19 who showed through elegant studies that FLT3 may be a direct target of MLL-AF4. We have analyzed the most common FLT3 mutations found in acute leukemia but have not sequenced the entire FLT3 coding sequence, and therefore, although unlikely, 15 the presence of novel FLT3-activating mutations responsible for constitutive activation of FLT3 might not be completely excluded.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This increased FLT3 expression in the absence of FLT3-activating mutations suggests that the constitutive overexpression of FLT3 is a result of aberrantly increased transcription of FLT3 and it is not due to FLT3-activating mutations. This is supported by Guenther et al, 19 who showed through elegant studies that FLT3 may be a direct target of MLL-AF4. We have analyzed the most common FLT3 mutations found in acute leukemia but have not sequenced the entire FLT3 coding sequence, and therefore, although unlikely, 15 the presence of novel FLT3-activating mutations responsible for constitutive activation of FLT3 might not be completely excluded.…”
Section: Discussionmentioning
confidence: 62%
“…Despite this emerging controversy, FLT3 is consistently highly expressed in MLLrearranged ALL, and therefore it is not fully resolved whether the constitutive activation of FLT3 in MLL-rearranged ALL is due to the presence of activating FLT3 mutations, or simply due to a transcriptional increased expression of FLT3 in an attempt to provide blast cells with survival and proliferative advantage. The latter has been recently suggested by Guenther et al, 19 by showing through elegant studies that FLT3 may be a direct target of MLL-AF4. 1 Interestingly, there is little information about the prognostic significance of FLT3 expression and mutational status in cytogenetically distinct subgroups of ALLs.…”
Section: Introductionmentioning
confidence: 82%
“…Importantly, Guenther et al [36] recently reported a list of 42 direct targets of MLL-AF4. Despite constituting different experimental approaches (non-transformed hESCs vs fully transformed leukemia cell lines), we have compared our GEP with the MLL-AF4 direct targets proposed by Guenther et al [36] and found that 8 (ERG, TNRC18, ADAM10, HOXA10, HOXA9, MEIS1, MEF2C, ZEB2) out of these 42 (20%) MLL-AF4 direct targets were also upregulated in our experimental system.…”
Section: Discussionmentioning
confidence: 99%
“…In this manner, DOT1L is recruited to gene locations normally under the control of MLL (Okada et al, 2005;Mueller et al, 2007;Monroe et al, 2011). DOT1L catalyzes the specific methylation of histone H3 at lysine 79 (H3K79), and this site-specific marking of histone H3 leads to transcriptional activation (Milne et al, 2005;Okada et al, 2005;Guenther et al, 2008;Krivtsov et al, 2008;Mueller et al, 2009;Thiel et al, 2010;Monroe et al, 2011;Nguyen et al, 2011). It has therefore been speculated that DOT1L enzymatic activity represents an oncogenic driver of MLL-r leukemia, and that inhibition of the DOT1L enzyme would represent a cogent approach to therapeutic intervention for MLL-r patients.…”
Section: Introductionmentioning
confidence: 99%